Stress Reduction in Sputtered Thin NiFe 81/19 Layers for Magnetic Field Sensors. (2016) - Jogschies, L.; Rittinger, J.; Klaas, D.; Wurz, M.C.
Abstract: Flexible magnetic field sensors using the anisotropic magnetoresistive effect that have been developed within the Collaborative Research Center 653 are to be transferred into industrial applications. Occurring challenges result from interactions between the flexible polyimide substrate and the functional layer namely a thin NiFe 81/19 film deposited by a DC sputter process. We have optimized the DC sputter process with regard to stress and roughness reduction.